Attuning to Children’s Layered Life-Making Through Relational Learning and Assessment (LEARNing Landscapes, 2024)
Interweaving my thinking with childhood stories of schooling, familial narratives, and experiences as a teacher alongside children, this article makes visible how my pedagogical approaches and desires for children to experience belonging shape my intentional work to recraft marginalizing curricula and assessment practices. In sharing my learning, unlearning, and continued growth, I endeavor to prompt a rethinking of how we, pre-service teachers, fellow educators, and school leaders, support children’s life‑making and wellbeing on school landscapes and offer approaches for all children to be centered as knowledge holders.
Keywords: assessment; curricula; inquiry; life-making